KUALITAS PELAYANAN UJI LABORATORIUM PASIEN RAWAT JALAN DI LABORATORIUM RSUP DR. SARDJITO YOGYAKARTA - Ningrum, Marlinda Retno Budya; Sayekti, Lulu Anastesi (PARADIGMA: Jurnal Ilmu Administrasi, 2023)
This research using a qualitative descriptive method. Data collection techniques were carried out using observation, interviews and documentation techniques. Data analysis in this research uses three components consisting of data reduction, data presentation, and drawing conclusions. The research results showed that the quality of outpatient laboratory testing services at the Dr. RSUP Laboratory Dr. Sardjito Yogyakarta is in the good category but not yet optimal because there are still several sub-indicators that have not run according to community expectations, namely the sub-indicator of ease of process in service, the sub-indicator of service standards which is considered unclear, the sub-indicator of speed service and also the sub-indicator of serving patients without discriminatory. Factors that hamper the quality of outpatient laboratory testing services at the Dr. Sardjito Hospital Yogyakarta Laboratory are patient awareness, unclear SOP, and lack of service staff.Keyword: Service Quality; Dr. Sardjito Hospital Laboratory.